FBXW7 regulates MYRF levels to control myelin capacity and homeostasis in the adult central nervous system - Hannah Y. Collins; Ryan A. Doan; Jiaxing Li; Jason E. Early; Megan E. Madden; Tyrell Simkins; David A. Lyons; Kelly R. Monk; Ben Emery (Nature Communications)
Abstract Myelin, along with the oligodendrocytes (OLs) that produce it, is essential for proper central nervous system (CNS) function in vertebrates. Although the accurate targeting of myelin to axons and its maintenance are critical for CNS performance, the molecular pathways that regulate these processes remain poorly understood. Through a combination of zebrafish genetics, mouse models, and primary OL cultures, we find that FBXW7, a recognition subunit of an E3 ubiquitin ligase complex, is a regulator of adult myelination in the CNS. Loss of Fbxw7 in myelinating OLs results in increased myelin sheath lengths with no change in myelin thickness. As the animals age, they develop progressive abnormalities including myelin outfolds, disrupted paranodal organization, and ectopic ensheathment of neuronal cell bodies with myelin. Through biochemical studies we find that FBXW7 directly binds and degrades the N-terminus of Myelin Regulatory Factor (N-MYRF), to control the balance between OL myelin growth and homeostasis.